СУЕВЕРИЯ (Scientific journal of the Fergana State University, 2023)
This article, focuses on  one of the most important issues of our time, folk customs which in fiction are  called superstitions and in common parlance-  irim-sirim . The author tried to declare superstition as an independent genre of folklore,  classify them according to their themes and content,  explore  the sources of their origin,  show how they correspond to the reality of life or they are based on superstitions.